2000
DOI: 10.1021/jp0023819
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the MoS2 (100) Surface:  A Chemical Potential Analysis of Sulfur and Hydrogen Coverage

Abstract: The stability of the (100) MoS2 surface has been studied using periodic DFT calculations taking into account various parameters such as the temperature and the partial pressure ratios of H2 and H2S present in the surrounding atmosphere. It appears that the sulfur coverage of the surface is strongly dependent on the H2/H2S ratio and that under working conditions, the most stable surface does not contain any coordinately unsaturated sites (CUS). Direct comparisons with experimental literature data such as EXAFS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
172
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(182 citation statements)
references
References 32 publications
9
172
0
Order By: Relevance
“…They found that under reductive condition adsorption of one CO molecule at the sulfur edge with about 50% S coverage is the most stable and exothermic by 0.7 eV. They also identified three thermodynamically stable surfaces for different H 2 /H 2 S pressure ratios which were also studied by Schweiger et al [24], Bollinger et al [27], Raybaud et al [33] and Cristol et al [34].…”
Section: Introductionmentioning
confidence: 84%
“…They found that under reductive condition adsorption of one CO molecule at the sulfur edge with about 50% S coverage is the most stable and exothermic by 0.7 eV. They also identified three thermodynamically stable surfaces for different H 2 /H 2 S pressure ratios which were also studied by Schweiger et al [24], Bollinger et al [27], Raybaud et al [33] and Cristol et al [34].…”
Section: Introductionmentioning
confidence: 84%
“…A k-point mesh (3,1,1) has been chosen to give an accurate sampling of the supercell's Brillouin zone. Previous studies [29][30][31] showed that this model is suitable to predict the electronic and structural properties of the MoS 2 surface. A vacuum layer of 15 Å is located above the MoS 2 slab in the z direction to avoid interactions between slabs.…”
Section: Methodsmentioning
confidence: 95%
“…The two upper rows were allowed to relax until forces acting on ions are smaller than 3.10 -2 eV.Å -1 . The two lower rows were kept fixed to simulate bulk constraints [29][30][31]. The promoted catalyst is modeled by substituting of the Mo atoms on the S edge and half of the atoms on the metallic edge by Co (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, with the recent developments of the computer simulations, new insights in the state of the HDS catalysts surface [81][82][83][84] as well as an overview of the HDS mechanism over the simulated surfaces were concurrently proposed [85,86]. Recently, we proposed for the first time a reliable CUS regeneration mechanism over MoS 2 crystallites by combining these two complementary methods [87,88].…”
Section: Introductionmentioning
confidence: 99%